The climate and health effects of a USA switch from coal to gas electricity generation. (15th August 2016) - Lueken, Roger; Klima, Kelly; Griffin, W. Michael; Apt, Jay
Abstract: Abundant natural gas at low prices has prompted industry and politicians to welcome gas as a 'bridge fuel' between today's coal-intensive electric power generation and a future low-carbon grid. We used existing national datasets and publicly available models to investigate the upper limit to the emission benefits of natural gas in the USA power sector. As a limiting case, we analyzed a switch of all USA coal plants to natural gas plants, occurring in 2016. The human health benefits of such a switch are substantial: SO2 emissions are reduced from the baseline (MATS (Mercury and Air Toxics Standard) retrofits by 2016) by more than 90%, and NOX emissions by more than 60%, reducing total national annual health damages by 20 – 50 billion annually. While the effect on global temperatures is small out to 2040, the USA power plant fleet's contribution could be changed by as much as −50% to +5% depending on the rate of fugitive CH4 emissions and efficiency of replacement gas plants.